2019
DOI: 10.2298/pan160504030d
|View full text |Cite
|
Sign up to set email alerts
|

The impact of agriculture on CO2 emissions in China

Abstract: This study empirically analyses the long-term relationship between agricultural production and carbon dioxide (CO2) emissions in China by using annual data covering1971-2010. In estimating the relationship between agriculture and CO2 emissions, the study also includes real income and energy consumption as variables in the model, in line with the Environmental Kuznet Curves (EKC) hypothesis. To identify the existence of a long-term relationship between CO2 emissions and agriculture, the bounds test approach for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(26 citation statements)
references
References 17 publications
5
21
0
Order By: Relevance
“…This case is observed in most developing economics in the scale-effect stage. These outcomes have been proven severally in the literature for the case of Turkey (Gökmenoğlu &Taspina, 2016), for the case of China (Doğan, 2018). Additionally, the same pattern was affirmed for the case of Pakistan in the studies of (Gökmenoğlu &Taspina, 2018).…”
Section: Empirical Results Interpretation and Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…This case is observed in most developing economics in the scale-effect stage. These outcomes have been proven severally in the literature for the case of Turkey (Gökmenoğlu &Taspina, 2016), for the case of China (Doğan, 2018). Additionally, the same pattern was affirmed for the case of Pakistan in the studies of (Gökmenoğlu &Taspina, 2018).…”
Section: Empirical Results Interpretation and Discussionmentioning
confidence: 52%
“…(1) Equation (1) provides the basic conceptual framework for investigating the theme under consideration and is based on (Gökmenoğlu & Taspina, 2018). Equation 1is augmented with agriculture to examine the agriculture-induced EKC for the case of Nigeria.This study uses agricultural value added as share GDP which previous studies like ( Gokemnoglu and Taspina, 2018;Doğan, 2018, Ullah et al,2018Doğan,2016) adopted. This study further improves on Gökmenoğlu and Taspina (2018) for the case of Pakistan and a similar study by Shahbaz et al (2014) for Tunisia.…”
Section: Data Description and Sourcementioning
confidence: 99%
“…Recent studies have been performed with various econometric methods to investigate the effects of agriculture on environmental degradation. Doğan ( 2018 ) utilized ARDL, FMOLS, DOLS, and CCR techniques to explore the relationship between agricultural production and CO 2 emissions in China by using annual data covering1971-2010. The findings from Doğan ( 2018 ) revealed that agriculture increases a country’s long term CO 2 emissions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to this study, the connection between both variables was inverted U-shaped. Doğan (2018) reports that in the long-term GDP, increases in carbon emissions decrease. According to the findings of (Anastacio, 2017), GDP squared positively and negatively impacts economic growth and approves the EKC theory.…”
Section: Resultsmentioning
confidence: 99%